2022
DOI: 10.1302/2633-1462.311.bjo-2022-0083.r1
|View full text |Cite
|
Sign up to set email alerts
|

Closed midshaft clavicle fractures

Abstract: Aims The management of mid-shaft clavicle fractures (MSCFs) has evolved over the last three decades. Controversy exists over which specific fracture patterns to treat and when. This review aims to synthesize the literature in order to formulate an appropriate management algorithm for these injuries in both adolescents and adults. Methods This is a systematic review of clinical studies comparing the outcomes of operative and nonoperative treatments for MSCFs in the past 15 years. The literature was searched usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…In this study, we found that the rate of non-union in non-operative patients was significantly higher compared to operative patients, which aligns with previous research [ 9 12 ]. A displacement distance of more than 2cm has been considered a relative indication for surgery [ 13 ], but in our centre, conservative treatment was always an option regardless of the degree of displacement. Through strict immobilization in the early stages and a well-designed rehabilitation strategy, we were able to achieve a controlled non-union rate of 12.7%, which is lower than previously reported data [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the rate of non-union in non-operative patients was significantly higher compared to operative patients, which aligns with previous research [ 9 12 ]. A displacement distance of more than 2cm has been considered a relative indication for surgery [ 13 ], but in our centre, conservative treatment was always an option regardless of the degree of displacement. Through strict immobilization in the early stages and a well-designed rehabilitation strategy, we were able to achieve a controlled non-union rate of 12.7%, which is lower than previously reported data [ 4 ].…”
Section: Discussionmentioning
confidence: 99%